Early trimesterprediction of hypertensive disorders in pregnancy using pregnancy associated plasma protein A - N., Usha B.; Prajwala, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The prediction of hypertension in first trimester is fairly a new concept in recent years , studies combining various parameters in the first trimester of pregnancy have been undertaken but an combination with high predictive value is to be developed. The objective of this study is to predict preeclampsia in first trimester using pregnancy associated plasma protein A. Methods: A prospective cohort study was done at the department of obstetrics and gynaecology JJM medical college, Davangere, Karnataka with pregnant women attending the antenatal OPD at 11-14 weeks of gestation. A pre-formed questionnaire was filled for the enrolled women then blood pressure was recorded, pregnancy associated plasma protein A (PAPPA) done at 11-14 weeks of pregnancy. IBM SPSS version 22 for windows was used for statistical analysis of data. Results: Low PAPPA itself is not a strong indicator of preeclampsia; studies have previously shown a significant improvement in detection by combining with other biophysical, biochemical parameters. Conclusions: In the present study, PAPPA was not found to be the predictor of preeclampsia.